Raw Material Storage Information System Case Study: CV.Bplast Jaya - Aldo Ardiansyah; Arif Senja Fitrani; Ade Eviyanti; Novia Ariyanti (CV. Media Digital Publikasi Indonesia, 2026)
This study was motivated by the limitations of the raw material inventory management system in companies, which is still carried out manually. The lack of understanding and knowledge of information technology among employees is also a factor hindering the implementation of a more efficient system. This condition causes various obstacles, such as delays in recording, inaccurate data, and difficulties in real-time stock tracking. The purpose of this study is to assist companies in developing a more effective and efficient raw material storage system through the use of web-based information technology. This study uses a qualitative approach with data collection methods in the form of observation, interviews, and documentation to obtain information related to system requirements and problems faced by companies. Based on the results of the research, a web-based raw material storage information system has been successfully designed and developed that is capable of presenting real-time inventory data, recording the entry and exit of raw materials more accurately, and providing search and reporting features that facilitate decision-making by management. The implementation of this system has shown an increase in data recording efficiency, a reduction in input errors, and ease in tracking raw material stocks. Thus, the developed system can be the right solution to overcome the raw material management problems that the company has been facing.